Electrowetting on conductors: anatomy of the phenomenon. (24th April 2017) - Ounnunkad, Kontad; Patten, Hollie V.; Velický, Matěj; Farquhar, Anna K.; Brooksby, Paula A.; Downard, Alison J.; Dryfe, Robert A. W.
Abstract : We have recently reported that reversible electrowetting can be observed on the basal plane of graphite, without the presence of a dielectric layer, in both liquid/air and liquid/liquid configurations. The influence of carbon structure on the wetting phenomenon is investigated in more detail here. Specifically, it is shown that the adsorption of adventitious impurities on the graphite surface markedly suppresses the electrowetting response. Similarly, the use of pyrolysed carbon films, although exhibiting a roughness below the threshold previously identified as the barrier to wetting on basal plane graphite, does not give a noticeable electrowetting response, which leads us to conclude that specific interactions at the water–graphite interface as well as graphite crystallinity are responsible for the reversible response seen in the latter case. Preliminary experiments on mechanically exfoliated and chemical vapour deposition grown graphene are also reported.